Efeitos modulatórios do óleo de alho (allium sativum), da acupuntura e da eletroacupuntura no estresse oxidativo e na inflamação induzidos por gentamicina no rim do rato - Souza, Mariana Rodrigues (2016)
The aminoglycoside gentamicin (GM) has major role in the treatment of serious infections, produced by gram-negative bacilli, despite its toxic effect. The specificity of the GM for renal toxicity is related to its accumulation in renal proximal tubule, causing a number of morphological and biochemical changes in humans and experimental animals. Garlic (Allium sativum), has many biological activities, such as anticancer, antimicrobial, antihypertensive, immunomodulatory and antioxidant activities. In the presence of oxidative stress the garlic oil (GO) modulates levels of antioxidants and lipid peroxidation, acting on elimination of free radicals.Acupuncture (Ac) is a therapeutic modality originating in ancient China. The electroacupuncture (EAc) is a therapeutic method used to potentiate the effects of acupuncture and consists of the application of low-intensity electric current and variable frequency in metallic needles inserted in the body of the animal or human being. For assessment of antioxidant and anti-inflammatory activity of GO, Ac and EAc ,a prospective, controlled and comparative study was carried out in Wistar rats submitted to the nephrotoxic effects of GM.Thirty male rats, aged from 12 to 14 weeks and weight ranging 267-373 g were randomly distributed into five groups of six animals: G1(control), G2- garlic oil, G3 Ac, G4 EAc2 (electroacupuncture 2 Hz), G5-EAc100 (electroacupuncture100 Hz). All the rats received GM (ip 100mgKg) during 5 consecutive daysfor the induction of nephrotoxicity. On the 7th day of the experiment, G3-G5 rats were treated with Ac and EAC (2hz / 100 hz) during 20 minutes, every other day, for 10 days.G1 rats were treated with olive oil by gavage. Arterial blood samples and the right kidney were collected 48 hours after the end of the experiment, under anesthesia with chloral hydrate. Parameters analyzed included blood urea and creatinine, malondialdehyde (MDA), reduced glutathione (GSH) and myeloperoxidase (MPO).Next the rats were killed by triple dose of anesthetic. G1 urea and creatinine values were similar to normal values known, suggesting that the toxic lesions were of lower intensity possibly due to a short period of induced toxicity.There was a significant increase of plasma and tissue concentrations of GSH in groups G4 and G5, compared to positive control. No differences were observed in serum MDA concentrations. In addition, there was significant increase of renal MDA, when comparing groups G5 versus G1 control, suggesting that electrical stimulation using 100 Hz can induce increased lipoperoxidation. There was significant reduction of MPO activity in the kidney of rats from groups G4 and G5. These findings confirm the anti-inflammatory activity of the EAc. It is concluded that, in this model, the OA and Ac do not induce protective effects on oxidative stress or inflammation and that the electric stimulation (2/100 Hz) reduce the oxidative stress while the EAc 100 Hz increases lipoperoxidation in kidney tissue. Keywords:Gentamicin; Oxidative stress; Inflammation; Acupuncture; Eletroacupuncture.